Peramalan Penyediaan dan Konsumsi Bahan Bakar Minyak Indonesia dengan Model Sistem Dinamik - Sa’adah, Ana Fitriyatus; Fauzi, Akhmad; Juanda, Bambang (UI Scholars Hub, 2017)
This study contributes to the existing literature of oil industries in Indonesia by examining fuel supply and consumption in Indonesia. The objectives of this research were to predict fuel supply and consumption in Indonesia in the future. The model formed in this research was system dynamic. The simulation result showed that until 2016, fuel oil supply can meet the fuel oil consumption. From 2017 to 2025, fuel oil supply cannot meet domestic fuel oil consumption. In 2025, fuel oil supply is estimated up to 651.092 million barrel and fuel oil consumption is up to 719.048 million barrel.